Comparison of IgG4 with inflammatory cytokines (IL-1, IL-6 and TNFα) in rheumatoid arthritis - Sakthiswary, Rajalingham; Shaharir, Syahrul; Abdul Wahab, Asrul; Uma Rajeswaran, Veshaaliini (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is an autoimmune disorder characterized by chronic joint inflammation driven by a complex interplay of autoantibodies, cytokines, and chemokines. While the role of proinflammatory cytokines, such as interleukin-1(IL-1), interleukin-6(IL-6), and tumor necrosis factor-α (TNF-α), in the pathogenesis of RA has been well-established, the contribution of the immunoglobulin G subclass IgG4 remains a topic of ongoing investigation. This cross sectional study aim was to compare the levels of IgG4 and these key inflammatory cytokines in Malaysian patients with RA.MethodsThe study enrolled a total of 194 RA patients. All subjects were tested for their serum IgG4, IL-1, IL-6 and TNF-α levels. Besides, subjects were assessed for their disease activity based on DAS28, functional disability based on HAQ-DI (Health Assessment Questionnaire-Disability Index) and the severity of the radiographic joint erosions by using the Modified Sharp Score (MSS).ResultsCorrelation analysis revealed a moderate positive association between IgG4 and IL-6 levels (r=0.348, p=0.001), but there were no significant correlations with IL-1 and TNFα levels. IgG4 levels showed a significant positive correlation with DAS28, MSS, and HAQ-DI. All 3 cytokine levels had significant relationships with the DAS28 scores, but for the MSS, only TNF-α (p=0.024) and IL-6 (p=0.016) demonstrated significant associations. None of the cytokines correlated significantly with the HAQ-DI scores.ConclusionThe positive correlation between IgG4 and IL-6 levels underscores the possibility for IL-6-driven pathways to influence IgG4 production. Serum IgG4 was associated with more clinical aspects of RA compared to the classical inflammatory cytokines.